PERSEPSI PETANI PADI SAWAH TERHADAP KINERJA PENYULUH PERTANIAN DI DESA TATENGESAN KECAMATAN PUSOMAEN KABUPATEN MINAHASA TENGGARA - Anggi Ravy Tanauma; Welson Marthen Wangke; Elsje Pauline Manginsela (AGRI-SOSIOEKONOMI, 2019)
This study aims to determine the perceptions of farmers in rice fields on the performance of agricultural extension workers in Tatengesan Village, Pusomaen District, Southeast Minahasa Regency. This research wasconducted for 3 months from March to May 2019. The data used in this study are primary data and secondary data. Primary data collection through interviews and filling out questionnaires with 9 direct questions to 20 respondents of lowland rice farmers. Secondary data was obtained from related institutions, namely the Agricultural Extension Office (BPP), the Old Law Office and the Pusomaen District Office of SoutheastMinahasa Regency, the Internet through google searching and google book, to obtain journal books and articles related to research topics, namely perceptions of lowland rice farmers on the performance ofagricultural extension agents. Data analysis carried out in the study was descriptive analysis using a Likert Scale. The results of the study using a Likert Scale showed that the index numbers of perceptions of lowlandrice farmers on the performance of agricultural extension workers were at the point of 57.96% which was included in the satisfied category. *eprm*